Yūsuf-i Hindī qaid-i farang meṉ : yaʻnī, Navvāb Najmuddaulah Dabīrulmulk Mirzā Asadullāh Ḵẖāṉ Niẓām Jang Bahādur G̲ẖālib ke vāqiʻah-yi qaid ke ḥālāt - Muḥsin bin Shabbīr (SAMP early 20th-century Indian books project, 1933)
Biography of Mirza Asadullah Khan Ghalib, 1797-1869, Urdu poet.